2019
DOI: 10.3348/kjr.2018.0812
|View full text |Cite
|
Sign up to set email alerts
|

Technical Performance of Two-Dimensional Shear Wave Elastography for Measuring Liver Stiffness: A Systematic Review and Meta-Analysis

Abstract: Objective To assess the technical performance of two-dimensional shear wave elastography (2D-SWE) for measuring liver stiffness. Materials and Methods The Ovid-MEDLINE and EMBASE databases were searched for studies reporting the technical performance of 2D-SWE, including concerns with technical failures, unreliable measurements, interobserver reliability, and/or intraobserver reliability, published until June 30, 2018. The pooled proportion of technical failure and unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 60 publications
3
34
0
3
Order By: Relevance
“…Although many studies, including meta-analysis [16], have shown that liver elasticity measured by SWE is related to the pathological stage of fibrosis, the accuracy and diagnostic thresholds based on SWE are still controversial and the quality criteria and optimal number of measurements need to be defined [17]. Therefore, we performed a meta-analysis to assess the overall performance of SWE in the diagnosis of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies, including meta-analysis [16], have shown that liver elasticity measured by SWE is related to the pathological stage of fibrosis, the accuracy and diagnostic thresholds based on SWE are still controversial and the quality criteria and optimal number of measurements need to be defined [17]. Therefore, we performed a meta-analysis to assess the overall performance of SWE in the diagnosis of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of shear wave propagation and data filling of the sample box were performed 3 times for each patient, and each set of shear wave propagation data included one or two ROIs: Therefore, we measured liver stiffness and the SWD 3 to 6 times for each patient. If a bizarre pattern of shear wave propagation was observed or the color layer was absent in the ROIs, SWI was considered as a technical failure [16][17][18]. For each patient, we calculated an interquartile range interval (IQR), and considered measurements with IQR values less than 30% as reliable [16].…”
Section: Us Examinations Using 2d-swimentioning
confidence: 99%
“…Liver SWE has been increasingly used as a quantitative biomarker for evaluating new drugs or treatments, such as anti-viral agents and anti-fibrotic agents [4]. In the clinical field, the physics and manufacturing techniques, measurement variability, quality criteria, and procedures for performing elastography have been extensively investigated, and have now become standardized through the emergence of an international consensus [5][6][7]. As such, the World Federation for Ultrasound in Medicine and Biology (WFUMB) issued guidelines on the use of SWE for the assessment of liver diseases in 2015 and 2018 [8,9].…”
Section: Introductionmentioning
confidence: 99%